A cross-cultural study of high-altitude botanical resources among diverse ethnic groups in Kashmir Himalaya, India - Shiekh Marifatul Haq; Muhammad Waheed; Aadil Abdullah Khoja; Muhammad Shoaib Amjad; Rainer W. Bussmann; Kishwar Ali (BMC, 2023)
Abstract Background In the Himalayas, traditional knowledge and biodiversity are strongly linked due to the symbiotic interaction between plant and cultural diversity, as well as the support provided by cultural memories, ecological awareness, and social norms. Our study was focused on documenting the vanishing knowledge in the Kashmir Himalaya with the following main objectives: 1) to document the ethnomedical and cultural knowledge of the local flora, 2) to evaluate the cross-cultural use of the flora in the region, and, finally, 3) to identify the key indicator species utilized by each ethnic group using multivariate statistical analysis. Methods We used semi-structured questionnaires to conduct interviews with people of different ethnicity, gender, age, and occupational categories. The intercultural relationships of species utilization among ethnic groups were examined using a Venn diagram. The overall trends between the indicator values and the plant species used by diverse ethnic groups were illustrated using the linear regression model. Results We recorded 46 species belonging to 25 different families used by the local people of the Kashmir Valley belonging to four ethnic groups (Gujjar, Bakarwal, Pahari, and Kashmiri). The dominant families recorded were Asteraceae and Ranunculaceae followed by Caprifoliaceae. Rhizomes were the most utilized plant part, followed by leaves. A total of 33 ailments were treated with plants, and gastrointestinal disorders were treated with most species followed by musculoskeletal diseases and dermatological problems. Across cultural relationships, the Gujjar and Pahari showed greater similarity (17%). This may be due to the fact that both ethnic groups share a common geographical landscape and are exogamous to each other. We identified key indicator species used by different ethnic groups with significant (p ≤ 0.05) values. For instance, in the Gujjar ethnic group, Aconitum heterophyllum and Phytolacca acinosa had significant indicator value, which was due to the fact that these plants were easily accessible and also had a wide range of uses. In contrast, the Bakarwal ethnic group showed different indicator species, with Rheum spiciforme and Rhododendron campanulatum being highly significant (p ≤ 0.05), because this ethnic group spends the majority of their time in high-altitude pastures, using a particularly wide variety of plant species for medicine, food, and fuelwood. While indicator values and plant usage were positively correlated for the Gujjar, Kashmiri, and Pahari ethnic groups, they were negatively correlated for the Bakarwal. The positive correlation indicates cultural preferences for certain plant use and underlines the cultural significance of each species. The current study reported new uses for the following species: raw roots of Jurinea dolomiaea used for tooth cleaning, seeds of Verbascum thapsus applied for respiratory diseases, and flowers of Saussurea simpsoniana given to anyone as a good luck wish. Conclusion The current study highlights historical ethnic group stratifications and cultural standing while comparing reported taxa across cultures. Each ethnic group made extensive ethnomedical use of plants, and knowledge, originally transmitted verbally, is now available in writing for reference. This could pave the way for providing incentives to local communities to showcase their talents, celebrate them, and gain from potential development initiatives.